Sentiment Analysis of Indonesian Presidential Candidate 2024 on Facebook - Fattah, Fardhan Saifullah; Ratnasari, Chanifah Indah (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The 2024 Indonesian Presidential Election has become a hot topic in daily life, including on Facebook. Everyone has the freedom to express or speak their opinions on the Indonesian presidential candidate for 2024. As a result, there are a variety of viewpoints, some of which are positive and some of which are negative. This research aims to classify positive and negative sentiments in each presidential candidate's Facebook post comment data. Several processes are involved in this sentiment analysis process, including data scraping, data preprocessing, data labeling, and data classification using the Support Vector Machine (SVM) approach. The data used are comments obtained from each presidential candidate's Facebook page between July 1 and July 31, 2023. Anies Baswedan, with a positive sentiment value of 88.20% and a negative sentiment value of 11.80%, is the presidential candidate with the highest positive sentiment and the lowest negative sentiment. The SVM approach with a linear kernel produced the best precision value for positive sentiment, namely 94%.